2020
DOI: 10.1177/2325967120911731
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Shortens Return to Play in National Football League Players With Acute Hamstring Injuries

Abstract: Background: Hamstring injuries are prevalent in professional athletes and can lead to significant time loss, with recurrent injury being common. The efficacy of platelet-rich plasma (PRP) for augmentation of nonoperative treatment of partial musculotendinous hamstring injuries is not well established. Hypothesis: The addition of PRP injections to nonoperative treatment for acute partial musculotendinous hamstring injuries will lead to a shortened return to play in National Football League (NFL) players. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Although 3 studies found patients receiving PRP achieved earlier RTP than controls by 10 to 15 days, 1 , 16 , 33 5 studies showed no such effect. 21 , 37 , 39 , 65 , 66 Despite finding no relationships between PRP injection and days or practices missed because of hamstring injury in National Football League athletes, Bradley et al 21 reported PRP injection to be associated with fewer games missed. Zanon et al 89 noted a decreased reinjury rate in patients receiving PRP in the short term; however, the long-term rate was not different from that of controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 3 studies found patients receiving PRP achieved earlier RTP than controls by 10 to 15 days, 1 , 16 , 33 5 studies showed no such effect. 21 , 37 , 39 , 65 , 66 Despite finding no relationships between PRP injection and days or practices missed because of hamstring injury in National Football League athletes, Bradley et al 21 reported PRP injection to be associated with fewer games missed. Zanon et al 89 noted a decreased reinjury rate in patients receiving PRP in the short term; however, the long-term rate was not different from that of controls.…”
Section: Resultsmentioning
confidence: 99%
“… ** References 3, 4, 11 21, 23, 26, 33, 37, 39, 41, 42, 46 54, 56 58, 62, 65, 66, 68, 70, 72, 73, 77, 81, 82, 87 89. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated the clinical efficacy of local platelet-rich plasma (PRP) administration for muscle injury treatment [ 19 , 20 , 21 , 22 , 23 ]. The effect of PRP is mediated by the platelet alpha-granules, which contain various growth factors, e.g., FGF-2, HGF, and TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“… 20 In addition, a large number of unproven therapies are being marketed directly to athletes, with unsubstantiated claims of efficacy and lack of information about risks, product manufacturing, and unrealistic expectations of outcomes. 27 While efforts have been made to evaluate biologic treatments in NFL athletes, 5 the considerable challenges of performing research on these players mean that there are currently few high-level studies to guide treatments. 20 …”
mentioning
confidence: 99%